Answer:
Jason is 14 year old.
Explanation:
Given: Joe, John and Jason are each a year apart in age.
Sum of their age is 39.
Lets assume the age of Joe be x
∴ Age of Jahn will be
![(x+1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9sihokhax7uddflaoklmlvcxb2wavxgq9k.png)
And age of Jason will be
![(x+2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/sgix3fsx6dhtz5v4t7o49oawvfqkkrh5wh.png)
Now, putting up an equation for the sum of their age.
∴
![x+(x+1)+(x+2)= 39](https://img.qammunity.org/2021/formulas/mathematics/middle-school/98amf18afmpcopav2cguw01agxlmk9pjkc.png)
Opening the parenthesis.
⇒
![x+x+1+x+2= 39](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6jkc6nzk2a85x3oyh5wc4a6b7zjinvcyxo.png)
⇒
![3x+3= 39](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8t9kxepsp0w394kh07ruqpqxc3z03frtir.png)
Subtracting both side by 3
⇒
![3x= 36](https://img.qammunity.org/2021/formulas/mathematics/middle-school/y0lemrbqxmdde64iftp6mkdlqojohda42z.png)
Dividing both side by 3
⇒
![x= (36)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/x1bduf4319e0hweqla2yip7f8ikrv3hyy9.png)
∴
![x= 12\ years](https://img.qammunity.org/2021/formulas/mathematics/middle-school/m4wh52ahx8shjg7420nk0ipesr3ksq9qwt.png)
Hence, Joe is 12 year old.
Next subtituting the value of x to find age of Jason and John.
Jason=
![(x+2)= 12+2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zu0dhepj135rzytvvpi3lg4luax71fdokn.png)
∴Jason= 14 years.
John age=
![(x+1)= 12+1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/s1elfzeqd24i49bh076y5ck9g6h9gzkc7r.png)
∴ John Age= 13 years.
Hence, Jason is 14 year of age.